Downregulated androgen receptor expression in preputial tissues of children with hypospadias - Yang, Zhilin; Zhang, Peiliang; Zhang, Tiejun; Yin, Jianchun; Zhou, Guanglun; Zhao, Weiguang; Chen, Pengyu; Li, Jiaqiang; Li, Shoulin (Frontiers in Pediatrics, 2025)
PurposeTo resolve conflicting evidence on androgen receptor (AR) expression in hypospadias, we compared preputial AR levels between affected children and controls.MethodsForty patients with isolated hypospadias (age 2.9 ± 0.79 years, range 1.6–5.2 years) and 40 normal boys (age 3.2 ± 0.79 years, range 1.8–4.7 years) who underwent circumcision for phimosis were included in our study. Inner plates of preputial tissues were analyzed by immunohistochemistry for AR detection.ResultsAR immunoreactivity was predominantly localized to the basal epithelial layer. Significantly reduced AR expression was observed in hypospadias patients vs. controls [average optical density (AOD), 0.38 ± 0.09 vs. 0.56 ± 0.11]. However, there was no difference in AR expression between the proximal and distal hypospadias (AOD, 0.40 ± 0.07 vs. 0.37 ± 0.10, P = 0.22).ConclusionsPreputial AR downregulation in hypospadias implicates AR deficiency in pathogenesis, providing evidence to resolve a key controversy in the field.